The power consumption profile to improve the kneading operation of unrefined wheat flour in bread-making. (November 2022) - Parenti, Ottavia; Zanoni, Bruno; Baldi, Fabio; Guerrini, Lorenzo
Abstract: The interest in unrefined wheat flours for bread production has largely increased due to the scientific evidence on the health benefits associated to their consumption. However, they often resulted in dough difficult to be worked and in end-products with poor technological quality, limiting the use of unrefined wheat flour and compromising the acceptability of unrefined bakery products. In this work flours from four wheat cultivars of different technological quality and refinement degree were studied, and a two-stage methodological approach was proposed as innovative method to improve the use of weak and unrefined flours in bread-making. Firstly, an optimization stage trial was applied to determine the optimal dough water amount and kneading time to maximize the bread specific volume. Secondly, a monitoring stage was applied to perform an on-line monitoring of the kneading operation in the real operating conditions using the power consumption profile method. The power consumption profile method was able to predict the "Optimal kneading time" (i.e., the peak of the power consumption profile), which was significantly correlated to the optimal kneading time determined by the previous optimization stage. Moreover, several characteristic parameters were derived from the dough power consumption profile of wheat flours with different technological quality and refinement degree. This work showed the potentiality of the power consumption profile method for a real-time monitoring of the kneading operation of unrefined and weak wheat flours. Graphical abstract: Image 1 Highlights: Kneading variables were optimized for flour refinement degree and cultivar. Optimized unrefined doughs showed the greatest Alveograph improvements. Kneading parameters from the power consumption curve were determined and analysed. Optimal kneading time from power consumption highly correlated with optimized time. Farinograph and power consumption parameters showed no correlations.